Analisis City Branding Kota Bitung Dalam Menarik Investor Dan Wisatawan - Mantiri, Maurits (JURNAL RISET BISNIS DAN MANAJEMEN, 2018)
The purpose of this research is study the implementation of strategy city branding city Bitung applied by a city government Bitung .Analyze strategy which should be achieved relating to city branding city Bitung in pulling attract investors and tourists .Research in do in a city Bitung the province of north sulawesi .This research using research quantitative with a model associative .The research results show that have the potential and excellence in the industrial sector , trade and tourism , city Bitung can having the identity strong as industrial city and tourism. The use of brand of Bitung nautical will with the festival charm the strait lembeh is one way to introduce to the public at large , about potential and is experiencing many benefits Bitung city that be an attraction for tourists and investors , hopefully with a brand it becomes a fastener and all components levels of society and the government in promoting the city BitungKeywords: Branding City, Investor, Tourist, Bitung City